Photography Strategies in the Challenges of Industry 4.0 and Society 5.0 - Samaratungga, Oscar; Kusrini, Kusrini (Jurnal Multidisiplin Sahombu, 2025)
Photography faced significant challenges during the COVID-19 pandemic due to restrictions on space for in-person meetings, while previous photo shoots required in-person meetings. During this period, technological and industrial developments began to be introduced in the era of Industry 4.0 and Society 5.0, but their popularity was overshadowed by information about COVID-19. This paper aims to determine the strategies of photographers in facing the challenges of Industry 4.0 and Society 5.0. The method used is qualitative, with data collection through archival/document studies and literature studies. Albert Joseph Toynbee's challenge and response theory is used to discuss these issues. COVID-19 has also influenced photography in finding strategies for professional photography practice. One of these is virtual photoshoots or remote photography. The challenges of photography have become increasingly complex with the emergence of Artificial Intelligence (AI). Photographers are also facing new challenges. This condition is addressed by considering the convenience offered by AI, namely, combining AI results with photography for photo functions used for promotions or business